Analisis Butir Soal Sumatif IPA Kelas VII SMP Negeri 3 Pontianak dengan Rasch Model Menggunakan Rstudio - Inayah Dzil Izzati Hartono; Kurnia Ningsih; Andi Besse Tenriawaru (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Item analysis is carried out to improve the quality of items through revision or discarding ineffective items. This study aims to determine the quality of the items of the Summative Assessment of Science Subjects Class VII SMP Negeri 3 Pontianak Academic Year 2022/2023. This research is a quantitative research with descriptive method. Data obtained through documentation in the form of student answer sheets tested to 135 students with 30 multiple choice questions analyzed in aspects of validity, reliability, difficulty level, and differentiability with the Rasch Model using the R Program, especially R-Studio. The results of the analysis show that the questions have good validity quality because there are only 28 items that fit (93%) and 2 items that do not fit (7%), the reliability is categorized as sufficient with a reliability value of 0.683, the level of difficulty is good because it has a level of difficulty that varies from the category of very difficult, difficult, easy and very easy, good distinguishing power because it distributes person ability into 5 scales, namely very low, low, medium, high and very high so that it can measure students with diverse abilities, so that based on the results of the analysis it can be judged that the questions have good quality with good validity, sufficient reliability, good difficulty level and good distinguishing power.